2020
DOI: 10.3390/su12229637
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Small-Scale Physical Model Parameters of Pavement Structure

Abstract: A large amount of the local and first-class road infrastructures in Central Europe lead through settled areas, such as villages or even historical cities and town centers. The vibrations generated by passing vehicles around the pavement spread to the subgrade to the environment and also affect civil engineering structures and buildings. We have decided to adopt the approach of small-scale modeling of the pavement with the subgrade. Small-scale physical modeling brings benefits, such as size reduction, simplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…An assembly with a precise integrating sound level meter for measuring the noise situation was placed in place B1H. The system uses verified acoustic software by Brüel and Kjaer (BK) [34,35]. Its distance from the nearest tram line track (K1) in the direction of Petržalka-Centre is about 3.0 m. The track of the K2 tram line in the direction of Centre-Petržalka is about 5.4 m away from point B1H.…”
Section: Measurement Methodology and Measuring Linementioning
confidence: 99%
“…An assembly with a precise integrating sound level meter for measuring the noise situation was placed in place B1H. The system uses verified acoustic software by Brüel and Kjaer (BK) [34,35]. Its distance from the nearest tram line track (K1) in the direction of Petržalka-Centre is about 3.0 m. The track of the K2 tram line in the direction of Centre-Petržalka is about 5.4 m away from point B1H.…”
Section: Measurement Methodology and Measuring Linementioning
confidence: 99%
“…Results showed that regardless of the thickness of the aggregate base course layer, the surface deformation was diminished when the geogrid membrane was placed at a distance equating to half of the radius of the loaded area (D = 0.5r). Previous studies (Valašková et al, [27]) investigated the modeling of the pavement at a small scale, including the subgrade, experimentally and numerically. To establish the bearing capacity and settlement, a static plate-load test is utilized.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure used in the evaluation of the research topic, where the concrete slab and the subsoil under the slab were tested with dynamic effects, can be applied to the layer treated with slag [27]. It would also be appropriate to use slag as a backfill material in a mechanically stabilized rock structure, as analyzed in the study by [28,29]. For a comprehensive analysis, it is necessary to know the volume of the slag material located on the site.…”
Section: Introductionmentioning
confidence: 99%